PENGARUH MODEL PEMBELAJARAN TIPE MAKE A MATCH BERBANTUAN BOOKWIDGET TERHADAP HASIL BELAJAR SISWA KELAS IV MATERI PANCASILA SD NEGERI LAMPEUNEURUT - Hayatun Husna; Nurmasyitah; Suci Fitriani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the low learning outcomes in Pancasila Education among fourth-grade students at SD Negeri Lampeuneurut, particularly on the values of Pancasila, due to less varied learning models and limited learning media that are predominantly static. This study aimed to determine the effect of the Make a Match learning model assisted by Bookwidget on the learning outcomes of fourth-grade students in Pancasila Education at SD Negeri Lampeuneurut. The research method was a quasi-experiment with a Nonequivalent Posttest-Only Control Group Design. Samples were selected using Intact Group Sampling, consisting of class IV A (25 students) as the experimental group and class IV B (25 students) as the control group. Data were collected through a multiple-choice posttest and analyzed using the Mann-Whitney test via SPSS 32. The results showed that the average posttest score of the experimental class (90,40)) was higher than the control class (77,20). Based on the hypothesis testing, the Asymp. Sig. (2-tailed) value was 0.001 < 0.05, meaning was rejected and was accepted. In conclusion, there is a significant influence of the Make a Match learning model assisted by Bookwidget on the learning outcomes of fourth-grade students on Pancasila material at SD Negeri Lampeuneurut.